Hidden leverage and a false sense of security - Paul Davies (Danish Institute for International Studies (DIIS), 2008)
The story of the current financial crisis is a story of liquidity, leverage and security. Liquidity in the system was far less real than was assumed, leverage had become too high, often by being dis-guised or hidden off balance sheet and the value of security or collateral was too much presumed to be unlikely to ever decline. The collapse of New Century Financial, a leading US subprime mortgage lender, can be seen as a micro-version of the sudden reversal of fortunes that befell the system as a whole. US subprime was not the cause of the collapse, but one of the most excessive and vulnerable parts of a system gripped by the same fever. This paper looks at the long-term economic and regulatory develop-ments that laid the ground and created the motivations for the broad-based credit bubble wit-nessed in the past decade. It looks at the central role of the US economy, the effects of some previous crises, the deregulation of banking and the role of newer 'controls' such as the focus on risk-based capital and the use of mark-to-market accounting. It also raises a question about the role of central banks as lender of last resort - and how that will continue to effect motiva-tions in banking.
Keywords: 330; Finanzmarktkrise; Kreditgeschäft; Hypothek; Bubbles; Bankenpolitik; Kapitalmarktliberalisierung